The role of personality traits and problem-solving strategies on altruism in university students - Oktar, Saliha (Academic Journal of Psychology and Counseling, 2025)
Altruism in society can reduce the problems caused by the decline of moral and humanistic values. To develop altruistic behavior, it is necessary to determine the personality traits and problem-solving ability that are likely to be associated with it. The aim of the study was to examine the role of personality traits and problem-solving strategies on altruism. A total of 454 university students (309 women and 145 men), chosen through a random selection method, participated in the research. The following scales were used for the study: Altruism Scale, Eysenck Personality Inventory-Extroversion Scale, and Social Problem-Solving Inventory-Short Form. No gender difference was found in altruism. Extroverts scored significantly higher than introverts on altruism and its subscales. According to the correlation analysis, there was a moderate positive relationship between altruism, extroversion, and social problem-solving skills. The regression analysis concluded that extroversion and social problem-solving skills explain 20% of the total variance in altruism. Extroversion and social problem-solving skills were found to significantly predict altruism. Future research should consider investigating possible moderating and mediating variables in the relationship between social problem-solving and altruism.